An evaluatory study of the methods used in the reconstruction of historical vegetation and land-use, with reference to part of East Sussex, England - Moffat, Brian (1984)
This thesis is directed towards an evaluation of the principal methods used in the reconstruction of historical vegetation and land use. It is argued here that previous reconstructions by many authors have employed only one or a very limited range of techniques, and that comparative evaluation of the resultant data and of the methods themselves has generally been lacking in such studies.